A4NH 2018 annual report highlights: Flagship 3 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2019)
This includes three highlights document for Flagship 3 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Contributing Research to Dialogues and Decision-Making Highlight 2: East African Community Policy Support on Aflatoxin Mitigation Highlight 3: Research Informs Design of $13 Million Investment in Improving Food Safety